In Situ Growth of 120 cm2 CH3NH3PbBr3 Perovskite Crystal Film on FTO Glass for Narrowband‐Photodetectors. Issue 16 (21st February 2017) - Rao, Hua‐Shang; Li, Wen‐Guang; Chen, Bai‐Xue; Kuang, Dai‐Bin; Su, Cheng‐Yong
Abstract : Organometal trihalide perovskites have been attracting intense attention due to their enthralling optoelectric characteristics. Thus far, most applications focus on polycrystalline perovskite, which however, is overshadowed by single crystal perovskite with superior properties such as low trap density, high mobility, and long carrier diffusion length. In spite of the inherent advantages and significant optoelectronic applications in solar cells and photodetectors, the fabrication of large‐area laminar perovskite single crystals is challenging. In this report, an ingenious space‐limited inverse temperature crystallization method is first demonstrated to the in situ synthesis of 120 cm 2 large‐area CH3 NH3 PbBr3 crystal film on fluorine‐doped tin oxide (FTO) glass. Such CH3 NH3 PbBr3 perovskite crystal film is successfully applied to narrowband photodetectors, which enables a broad linear response range of 10 −4 –10 2 mW cm −2, 3 dB cutoff frequency ( f 3 dB ) of ≈110 kHz, and high narrow response under low bias −1 V. Abstract : 120 cm 2 laminar CH3 NH3 PbBr3 perovskite crystal film is in situ grown on fluorine‐doped tin oxide (FTO) glass via an ingenious space‐limited inverse temperature crystallization method. Such a crystal film presents excellent electron mobility (μe ), trap density ( n trap ), and electron diffusion length ( L ) of 40.7 cm 2 s −1 V −1, 8.80 × 10 10 cm −3, and 6.4 µm, respectively, which shows efficient performance in narrowband photodetectors.